(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2024)
This article examines the main complex of modern methods of teaching foreign languages, showing the effectiveness of their application in for¬eign language lessons. All modern techniques are aimed at mastering students’ communication skills in English, which contribute to the understanding of spoken and written speech, as well as reading in English with reading comprehension.